APOE4 genetic burden and female sex impact immune profile in brain and periphery in aged mice. (1st February 2022) - Mishra, Aarti; Soto, Maira; Delatorre, Nicole; Rodgers, Kathleen E; Brinton, Roberta Diaz
Abstract: Background: APOE4 isoform and female sex are genetic risk factors for Alzheimer's disease (AD) with women APOE4 carriers being at greater and accelerated risk for developing AD than men. Inflammation contributes to the AD disease progression. Apolipoprotein E (ApoE), and endocrine aging in women are known to impact antigen presentation, microglial function, T cell activation and the systemic inflammatory profile. We hypothesize that the interaction of female sex and APOE4 isoform exacerbates inflammation and thereby be evident in microglial reactivity, loss of function and peripheral immune cell activation contributing to the at‐risk AD profile. Method: 18‐month‐old Humanized (h)APOE3/3, APOE3/4 and APOE4/4 male and female mice from the Jackson labs were used. Single cell suspension generated from blood, spleen and brain were analyzed using flow cytometry. In the brain, microglial phagocytosis, cellular reactive oxygen species (ROS) production, MHC‐II expression and lipid droplet accumulation was measured. T cell infiltration in the brain was also established. Additionally, metabolic flux assays on microglial cells. In the periphery, CD4 and CD8 T cell populations and T cell activation were quantified. Result: In the brain, microglia from hAPOE4/4 females had the highest expression of MHC‐II and significantly lower phagocytic activity in comparison to hAPOE4/4 males and hAPOE3/3 females. Coincident with increased microglial reactivity, significantly higher T cells were detected in hAPOE4/4 female brain in comparison to hAPOE3/3 males. Interestingly, neutral lipid droplet accumulation was significantly higher in hAPOE3/3 females in comparison to hAPOE3/4 females consistent with a profile of increased phagocytic activity. Peripheral immune profile from the blood and spleen indicated patterns consistent with the brain‐immune analyses. APOE4 genotype had a significant impact on the proportion of activated CD4 and CD8 T cells. Female hAPOE4/4 had significantly higher CD4+CD69+ and CD8+CD69+ T cells in comparison to hAPOE3/3 and hAPOE3/4 females in blood. In spleen, females across all the genotype had greater proportions of activated T cells, of which female hAPOE4/4 had the highest proportions of activated CD4 and CD8 T cells. Conclusion: The interaction of APOE4 genotype and sex affects the immune profile in the brain and periphery which is consistent with accelerated generation of at‐risk for AD immune profile.